PENGARUH RANGE OF MOTION AKTIF-ASSISITIF: LATIHAN FUNGSIONAL TANGAN TERHADAP PENINGKATAN KEKUATAN OTOT PASIEN STROKE NON HEMORAGIC DI RSUP HAJI ADAM MALIK MEDAN - Imelda Derang (Elisabeth Health Jurnal, 2020)
Introduction. Stroke is a central nervous system disorder that most often causes paralysis of the limbs, due to attacks on neuromuscular nerves that cause muscle weakness, so it takes practice that is ROM Active-Assistive hand-functional exercises. This study aims to determine the effect of Range Of Motion Active-Assistive Functional Exercise Hand on Increasing Muscle Strength In Non Hemorrhagic Stroke Patients at Haji Adam Malik General Hospital Medan.Method. research design was Quasi experimental with Pretest-posttest control group design approach. The number of samples was 30 respondents according to the inclusion criteria.Result. Wilcoxon statistical test results obtained the highest results on the pretest with the category of Fair (value 3) and postest with Good category (value 4) obtained p value = 0.001 where the value of p value α (≤0.05) so it can be concluded there is an effect Range Of Motion Active -Assistive Functional Hand Exercise on Increasing Muscle Strength in Non Hemorrhagic Stroke Patients and for the control group the results obtained p = 0.175, which means no increase in muscle strength before and after the study. Mann Whitney Test with p value of 0.001 where p value α (≤0,05)Duscussion. can be concluded that there is a significant difference between treatment group and control group. Subsequent studies are suggested to perform the same type of research on the range of motion of non hemorrhagic stroke patients.